Ultralow Specific on-Resistance Trench MOSFET with a U-Shaped Extended Gate - 王卓 李鹏程 张波 范远航 徐青 罗小蓉 (Chinese physics letters, 2015)
An ultralow specific on-resistance （Ron,sp） trench metal-oxide-semiconductor field effect transistor （MOSFET） with an improved off-state breakdown voltage （BV） is proposed. It features a U-shaped gate around the drift region and an oxide trench inserted in the drift region （UG MOSFET）. In the on-state, the U-shaped gate induces a high density electron accumulation layer along its sidewall, which provides a low-resistance current path from the source to the drain, realizing an ultralow Ron,sp. The value of Ron,sp is almost independent of the drift doping concentration, and thus the UG MOSFET breaks through the contradiction relationship between R p and the off-state BV. Moreover, the oxide trench folds the drift region, enabling the UG MOSFET to support a high BV with a shortened cell pitch. The UG MOSFET achieves an Ron,sp of 2 mΩ·cm^2 and an improved BV of 216 V, superior to the best existing state-of-the-art transistors at the same BV level